UKURAN PERUSAHAAN SEBAGAI PEMODERASI PENGARUH PROFITABILITAS DAN OPINI AUDIT TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) (StudiEmpirisPada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia (BEI) - Pradita Selviarini, 14.05.52.0279; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
The purpose of this study was to determine and analyze the effect of profitability, audit opinion, firm size and the firm size as a moderator. The firm size is expected to increase the effect of profitability and audit opinion.The independent variables in this study consist of profitability, audit opinion, and firm size. The dependent variable is audit delay, and as the moderating variable is firm size. In this study using sample manufacturing companies listed on the Bursa Efek Indonesia period 2014-2016. The sample of research as many as 198 companies. Method of return of sample using purposive sampling. Hypothesis testing in this study using the technique of Multiple Linear Regression analysis and Moderated Regression Analysis (MRA). The results of this study showed profitability and auditor opinion has a significant negative effect on audit delay. Firm size has an insignificant negative effect on audit delay. Firm size can moderate (reinforce) the relationship between profitability to audit delay, but firm size can not moderate the relationship between auditor opinion on audit delay. Keyword: Audit delay, Profitability, Auditor opinion, Firm Size